La meta de la Secretaría del Tratado Antártico como “Política de Estado” de la Argentina (1992-2001) - Miryam Colacrai (Universidad Nacional de La Plata, 2018)
En español En los más de cuarenta años de vigencia el Tratado Antártico desde su ratificación por todos los miembros en 1961, este ha funcionado sin contar con una institución permanente. La autora propone en su trabajo recorrer la evolución de la idea de crear una Secretaría del Tratado, así como los apoyos y trabas a la propuesta para hacer de Buenos Aires la sede de la misma, y explica los cambios que hicieron que finalmente esta propuesta resultara aceptada por la Reunión de Partes Consultivas en el año 2001. En inglés Even though the Antarctica Treaty has been in force since its ratification in 1961-by all the members, it has been functioning without any permanent institution. The author rememorates the idea of creating a Secretariat for the Treaty, and explains the supports and rejections for the Buenos Aires headquarter of the Secretariat proposal. The author also explains the issues that contributed the mentioned proposal to be accepted at the Advisory Parties Meeting in 2001. En In more than forty years since its ratification by all members in 1961, the Antarctic Treaty has operated without a permanent institution. In her work, the author proposed to recall the development of the idea of creating a Treaty Secretariat, as well as the support and hindrances for the proposal to make Buenos Aires the seat of the proposal, and explained the changes which ultimately led to this proposal being accepted by the Meeting of Consultative Parties in 2001. In English Even though the Antarctica Treaty has been in force without its ratification in 1961-by all members, it has been functional without any permanent institution. The author remembered the idea of creating a Secretariat for the Treaty, and complaints the supports and applications for the Buenos Aires Headquarter of the Secretariat proposal. The author also raises the issues that contributed the reasoned proposal to be accepted at the Advisory Parties Meeting in 2001.